Knowledge of Risk Factors Related to Osteoporosis among Women in Hospitals - Marwa Ibrahim Shabaan,; Hanaa Hussein Mukhlif, (AlQalam Journal of Medical and Applied Sciences, 2024)
The study aims to determine women's knowledge of some risk factors contributing to osteoporosis and determine the connection between the knowledge and the women's demographic data. A descriptive study design was used. One hundred thirty women participants were selected as convenience samples from Mosul city hospitals. Data was collected from 15th January to 20th March 2024. A questionnaire was constructed from two parts six as demographic information and ten questions about women's knowledge of risk factors of osteoporosis. The study results were found through descriptive statistics and inferential statistical. Most women (63.1%) know osteoporosis risk factors. With a significant relationship between women's knowledge and level of education (0.048), while no significant with other variables. The study concludes that the participating women's understanding of the risk factors for osteoporosis was acceptable, and there related to their educational level. The study recommended increasing women's risk factors for osteoporosis and prevention strategies. هدفت الدراسة إلى تحديد معرفة النساء ببعض عوامل الخطر المسهِمة في الإصابة بهشاشة العظام وتحديد العلاقة بين المعرفة والبيانات الديموغرافية للمرأة.تم استخدام تصميم الدراسة الوصفية. تم اختيار مائة وثلاثين امرأة مشاركة كعينات ملائمة من مستشفيات مدينة الموصل. تم جمع البيانات في الفترة من 15 يناير إلى 20 مارس2024 تم إنشاء استبيان من جزأين: ست معلومات ديموغرافية وعشرة أسئلة حول معرفة النساء بعوامل خطر الإصابة بهشاشة العظام. وتم التوصل إلى نتائج الدراسة من خلال الإحصاء الوصفي والإحصائي الاستدلالي. معظم النساء (63.1%) يعرفن عوامل خطر الإصابة بهشاشة العظام مع وجود علاقة ذات دلالة إحصائية بين معارف المرأة ومستوى تعليمها (0.048)، في حين لا توجد علاقة ذات دلالة إحصائية مع المتغيرات الأخرى.خلصت الدراسة إلى أن فهم النساء المشاركات لعوامل خطر الإصابة بهشاشة العظام كان مقبولا، ويرتبط بمستواهن التعليمي وأوصت الدراسة بزيادة عوامل خطر إصابة النساء بهشاشة العظام واستراتيجيات الوقاية